A streamlined synthesis of the neurosteroid 3β-methoxypregnenolone assisted by a statistical experimental design and automation. Issue 2 (5th December 2019) - Mancino, Valentina; Croci, Federico; Lozza, Anna Maria; Cerra, Bruno; Gioiello, Antimo
Abstract : The potential of integrating flow synthesizers, statistical design of experiments and automation has been exemplified to realize the streamlined etherification of pregnenolone to the neurosteroid 3β-methoxypregnenolone (MAP4343). Abstract : The potential of integrating flow synthesizers, statistical design of experiments and automation has been exemplified to realize the streamlined etherification of pregnenolone to the neurosteroid 3β-methoxypregnenolone (MAP4343). The use of Proton Sponge™, online reaction monitoring, work-up, product purification, and reagent recovery are additional key features of the present study. The optimized single-step process was validated by conducting a multistep sequence that has enabled the continuous flow synthesis of MAP4343 on a laboratory scale with an overall yield of 64% via six steps from the readily available plant-derived diosgenin.